ANALISIS MOTIVASI, LINGKUNGAN KERJA DAN KINERJA KARYAWAN : STUDI PADA PT. BARRIX SININDO JAKARTA - Aviantara, Muhammad Putra; Sumiyati, Sumiyati; Masharyono, Masharyono (Journal of Business Management Education (JBME), 2018)
Purpose - This research is conducted to know the description of motivation, work environment and employee performance of PT. Barrix Sinindo Jakarta.Design / methodology / approach - Unit of analysis in this study ie employees of PT. Barrix Sinindo Jakarta, totaling 30 people. Data collection techniques using questionnaires, While the data analysis techniques performed is descriptive and verifikatif analysis. The research method used is explanatory survey method.Findings - Based on the results of the study, it was found that job motivation in the high category to the score of 48,2%, work environment in the conducive category with the score of 39,8% and performance of employee was in the high category with the score of 49,4%Originality/value-Â  This study provides a basis for understanding the issues of motivation and work environment on performance of empliyee. The difference of this research with previous research is located on the object which is the company in expedition that is in PT. Barriq Sinindo Jakarta, with the variables studied motivation, work environment and performance of employee, and using theory or reference different from researcher previous.